Keynan Somali Equation Theory: An Empirical Attempt to Explain What Led to the Collapse of the Somali State - Issa-Salwe, Abdisalam M; Osman, Abdullahi Salah (Advances in Social Sciences Research Journal, 2024)
With the introduction of the contemporary state structure in Somalia, there have been and still are ways to explain what led to the collapse of the state. There have been many attempts from scholars who viewed the Somali case from different perspectives to explain what led to the state crumbling. The Somali state collapse has rejected conventional wisdom and evaded almost all attempts to impose a particular structure, explanation, or conclusion upon it. Much has been written and said about the country, particularly since 1991. One serious attempt which may help explain the Somali case is the Keynan Theory of Somali Equation (KSET). KSET is a philosophical attempt to explain the Somali state’s collapse by theorising the country’s political and social context, the factors that contributed to its demise, and the steps necessary for the Somali people to reconstruct their state. This paper will attempt to analyse and examine the theoretical framework of the phenomenon of social order fragmentation, which is the foundation of KSET. Applying the theory will further attempt to shed light on the factors that led to the establishment and continuation of Somali society. It will also examine "the complex of ideas, values, beliefs and institutions that define and underpin the Somali society" by looking at the methodology applied in KSET.